Wind Systems and Energy Balance in the Dead Sea Valley - Metzger, Jutta (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2017)
A new measurement concept was developed to determine the amount, variability and governing factors of evaporation from the Dead Sea. Additionally, a suitable indirect method to calculate evaporation is presented. Results show that vapour pressure deficit and wind speed are governing evaporation and that the diurnal cycle is determined by three distinct diurnal wind systems. The occurrence frequency and intensity of the wind systems are determined by local differential cooling and heating.